A Case of Bilateral Endobronchial Squamous Cell Carcinoma Mimicking Asthma - Sarkar, Anirban; Das, Anirban; Das, Sibes Kumar; Das, Soumya; Choudhury, Sabyasachi (Journal of Medicine, 2014)
Partial or complete obstruction of bronchial tree by endobronchial tumours results in obstructive hyperinflation, non resolving pneumonia, or atelectasis. Partial endobronchial obstruction may be associated with wheezes, which mimic asthmatic attack, non responding to inhaled medications. Here, we report a rare case of bilateral endobronchial squamous cell carcinoma, presenting with obstructive hyperinflation and wheezes, which was wrongly diagnosed as difficult asthma in a forty year old male. Histopathology of endobronchial biopsy tissue ultimately revealed the truth. DOI: http://dx.doi.org/10.3329/jom.v15i1.19875 J Medicine 2014; 15: 61-63